2014
DOI: 10.1007/s00467-014-2976-3
|View full text |Cite
|
Sign up to set email alerts
|

Early markers of obesity-related renal injury in childhood

Abstract: Childhood obesity has become a global epidemic. Recent epidemiological data suggest that obesity is associated with increased risk of renal injury in children. The onset of obesity-associated renal disease is insidious and asymptomatic, so early markers will be extremely useful in its prevention and treatment. Biomarker discovery can be focused on unbiased or biased (candidate) approaches. Unbiased approaches using innovative technologies, such as proteomics and metabolomics, have uncovered candidates that are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
1
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 19 publications
0
33
1
6
Order By: Relevance
“…6). A targeted metabolomics analysis in both experimental models (2,64) and the human condition of diabetes- (35,53,58) and obesity-related kidney disease (13,66,67) will be very useful to unravel in vivo regulation and translation of critical and relevant pathways of renal disease progression.…”
Section: Figmentioning
confidence: 99%
“…6). A targeted metabolomics analysis in both experimental models (2,64) and the human condition of diabetes- (35,53,58) and obesity-related kidney disease (13,66,67) will be very useful to unravel in vivo regulation and translation of critical and relevant pathways of renal disease progression.…”
Section: Figmentioning
confidence: 99%
“…In our study, renal tubular functions and GFR were not affected because neither creatinine nor BUN can change quickly enough during injury due to the fact that individuals with normal renal function have a functional reserve which compensates for nephron injury. 16 In numerous studies evaluating renal hypoxic injury, these values were also within normal limits. [4][5][6][7] The currrent opinion is that serum creatinine is considered to be a poor indicator of acute renal damage or injury.…”
Section: Discussionmentioning
confidence: 92%
“…This marker could provide detailed data before the occurrence of late consequences of injury like decrease in GFR. 16 Urinary NAG is a lysosomal enzyme that plays a role in the breakdown of glycoproteins in proximal renal tubular cells. It is a high molecular-weight lysosomal enzyme found in many tissues in the body.…”
Section: Discussionmentioning
confidence: 99%
“…It has been proven to be of great help to the study of obesity (Zhang et al ., ), to identify early and differential metabolic markers of obesity, and to understand mechanism of obesity occurrence and progression (Duggan et al ., ; Jung et al ., ; Kim et al ., ). Previous metabolomic studies have identified a few molecules to discriminate lean from individual subjects with obesity (Ding and Mak, ; Kim et al ., ; Oberbach et al ., ).…”
Section: Introductionmentioning
confidence: 99%